Experience of creation and perspectives of development of navigation equipment ТЛОИАСС (GPS) - Авсиевич, В. Н.; Гребенников, A. B.; Кокорин, В. И.; Новиков, В. Б.; Сушкин, И. Н. (Proceedings of National Aviation University (archive), 1999)
Considered are the materials on navigation equipment developed by Krasnoyarsk enterprise. Determined is the sphere of application of this equipment and principles of their operation are described